The Role of Human Resource Management in Improving Teacher Performance at TK Pancaran Berkat - Anggraeni, Rina; Prastowo, Sugeng Lubar (EDUCTUM: Journal Research, 2025)
This study analyzes the contribution of human resource (HRM) management to improving teacher performance at Pancaran Berkat Kindergarten and identifies factors that influence the effectiveness of HRM utilization in supporting learning quality. This study uses a qualitative descriptive approach and is designed as a case study. Data were collected through comprehensive interviews, participant observation, and documentation studies, with four teachers and the principal as key informants. The study shows that HRM tasks such as recruitment, training, performance appraisal, and incentives have been used regularly and have had a positive impact on improving teacher competence, discipline, and responsibility. Many factors influence how HRM functions in a school, including organizational culture, principal support, and teachers' own desires. These results indicate that effective HRM is not only administratively successful but also strategically successful in creating a positive work environment focused on improving the quality of early childhood education. The contribution of this study lies in its empirical understanding of how HRM practices in early childhood education institutions can serve as a model for developing strategies to continuously improve the quality of educators.